1998
DOI: 10.1055/s-0037-1615077
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine 3’:5’-Cyclic Monophosphate Induces Regulated Secretion of Tissue-Type Plasminogen Activator and von Willebrand Factor from Cultured Human Endothelial Cells

Abstract: SummaryThe effect of compounds increasing intracellular adenosine 3’:5’-cyclic monophosphate [cAMP]i levels (prostacyclin, isoproterenol, forskolin, cholera toxin), and of the cAMP analogs 8-bromo-cAMP and dibutyryl-cAMP, on the regulated secretion (acute release) of tissue-type plasminogen activator (tPA) and von Willebrand factor (vWF) was studied in cultured human umbilical vein endothelial cells (HUVEC).Prostacyclin, isoproterenol and forskolin, which increased [cAMP]i in HUVEC, and the cell-permeant cAMP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 14 publications
4
34
1
Order By: Relevance
“…37 Muldowney et al 37 reported that the endothelial-derived hyperpolarizing factor 5,6-epoxyeicosatrienoic acid induces the exocytosis of t-PA from storage granules via calcium-and cAMP-dependent pathways, in line with previous experimental findings. 38,39 According to our findings, 5,6-epoxyeicosatrienoic acid-mediated t-PA release was not affected by the ouabain-dependent part of the endothelial-derived hyperpolarizing factor pathway. 37 The major limitation of the present in vivo clinical study concerns the assessment of dynamic endothelial t-PA release in the forearm.…”
Section: Giannarelli Et Al No and Adrenergic-induced T-pa Release In supporting
confidence: 51%
“…37 Muldowney et al 37 reported that the endothelial-derived hyperpolarizing factor 5,6-epoxyeicosatrienoic acid induces the exocytosis of t-PA from storage granules via calcium-and cAMP-dependent pathways, in line with previous experimental findings. 38,39 According to our findings, 5,6-epoxyeicosatrienoic acid-mediated t-PA release was not affected by the ouabain-dependent part of the endothelial-derived hyperpolarizing factor pathway. 37 The major limitation of the present in vivo clinical study concerns the assessment of dynamic endothelial t-PA release in the forearm.…”
Section: Giannarelli Et Al No and Adrenergic-induced T-pa Release In supporting
confidence: 51%
“…4,5 For instance, histamine and thrombin have been shown to mediate secretion of WPBs by increasing the levels of cytosolic free Ca 21 , 6,7 whereas release of WPBs induced by secretagogues such as epinephrine or forskolin involves cAMP-dependent signaling. 8,9 Significant differences exist between Ca 21 -and cAMP-evoked WPB exocytosis and, whereas several cellular factors participating in the Ca 21 -regulated secretion of WPBs have been identified, much less is known about the molecular mechanisms underlying the cAMP-dependent exocytosis of WPBs.…”
Section: Introductionmentioning
confidence: 99%
“…24 In addition, agents that elevate intracellular cAMP such as vasopressin receptor agonists, purine nucleotides, epinephrine, and forskolin can also trigger the release of VWF. [25][26][27] The time course of cAMPstimulated VWF release is delayed compared with agonists that increase intracellular Ca 2ϩ . By inference, stimulation of VWF release should also occur in tandem with translocation of P-selectin to the cell surface, because both factors are located in the same secretory granule.…”
Section: Introductionmentioning
confidence: 99%